Karakteristik Iklim Di Kota Palembang Serta Implikasinya Terhadap Bencana Kabut Asap - Romadoni, Muhammad; Akhsan, Hamdi (Universitas Nurul Huda, 2022)
This research was conducted to determine the characteristics of the climate and its relationship to the haze disaster in the city of Palembang by utilizing data from the BMKG observation station, namely the Palembang Climatology Station and the Sultan Mahmud Baharudin II Meteorological Station, from 1981 to 2020. The research method used is secondary data research with a quantitative approach. The analysis used is according to the rules of the Expert Team on Climate Change Detection and indices ETCCDI. Trend analysis was carried out using the non-parametric Mankendal statistical and sens tests. The indices that experienced a significant trend were the temperature index, which indicates that the temperature in Palembang is increasing from time to time. The relationship between dry days has a correlation level of >0.9. This shows a close relationship between haze disasters and days without rain (CDD). The months prone to smog occur in June, July, August and September (JJAS).